Paremias in modern Spanish music: analysis of ``LOS40'' number 1 in 2023 - Cases Berbel, Elke (Romanica Olomucensia, 2024)
Music plays an important role in the development of human beings and, similarly to paremias, it is nourished by cultural heritage and serves to express emotions, criticisms, or value judgements. As current songs make use of modern language, studying the presence of paremias will indicate if the members of the younger Spanish population use this type of phraseological unit (PU) in their daily lives. To carry out this study, all the Spanish songs that reached the top of the list of ``LOS40'', the leading music radio station in Spain, were selected as a corpus. Once all the paremias had been extracted, they were divided into unaltered paremias, anti-proverbs, and simulated paremias. The anti-proverbs were classified according to the way they are de-automatised: by addition, by substitution, by permutation, and by reduction. Once the analysis of all the extracted paremias had been carried out, it was observed that the songs seek the presence of paremias to evoke the collective paremiological memory, but almost always through creative manipulation, either by means of deautomatisation (i.e. by anti-proverbs) or by means of a simulated proverb. For the creation of the simulated proverb, they make use of various stylistic resources to follow the poetic metre also used by the proverb, as well as its characteristic two-member structure. To sum up, the songs that were analysed seek to use paremias (47% of the songs had some), although because of their young and non-conformist spirit, they try to subvert the usual formula and give it an innovative, humorous, or transformative effect.
Keywords: paremia; anti-proverb; simulated proverb; modern songs; LOS40